2021
DOI: 10.3390/biomedicines9040331
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of STAT3 Transcription Factor by Synthetic Decoy ODNs on Autophagy in Renal Fibrosis

Abstract: Autophagy in the proximal tubules may promote fibrosis by activating tubular cell death, interstitial inflammation, and the production of pro-fibrotic factors. The signal transducer and activator of transcription 3 (STAT3) is activated as a potential transcription factor, which mediates the stimulation of renal fibrosis. We investigated the role of the STAT3 in autophagy and its effect on the prevention of interstitial renal fibrosis. In this study, we use synthesized STAT3 decoy oligonucleotides (ODN), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…We [14] demonstrated that mice with Atg7 knockout in proximal tubules had fewer atrophic tubules, less apoptosis, and less interstitial fibrosis during UUO. These initial findings are supported by follow-up studies [141][142][143], indicating that autophagy in kidney tubules promotes interstitial fibrosis. Mechanistically, autophagy may induce tubular cell death, cell cycle arrest, and senescence, resulting in the production and secretion of pro-fibrotic and pro-inflammatory cytokines to stimulate fibroblasts for fibrosis [14,138].…”
Section: Autophagy In Tubulointerstitial Fibrosismentioning
confidence: 67%
“…We [14] demonstrated that mice with Atg7 knockout in proximal tubules had fewer atrophic tubules, less apoptosis, and less interstitial fibrosis during UUO. These initial findings are supported by follow-up studies [141][142][143], indicating that autophagy in kidney tubules promotes interstitial fibrosis. Mechanistically, autophagy may induce tubular cell death, cell cycle arrest, and senescence, resulting in the production and secretion of pro-fibrotic and pro-inflammatory cytokines to stimulate fibroblasts for fibrosis [14,138].…”
Section: Autophagy In Tubulointerstitial Fibrosismentioning
confidence: 67%
“…In recent years, the relationship between autophagy and renal fibrosis has been reported in studies on renal inflammation and autophagy [ 22 , 24 , 34 ]. Autophagy is an important cellular mechanism for the intracellular lysosome-mediated degradation of damaged organelles, protein aggregates, and other macromolecules in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor EB (TFEB) is a master regulator of autophagy-related gene transcription, lysosome biogenesis, and autophagosome formations [ 39 , 40 , 41 , 42 ]. TFEB levels increase during inflammation and fibrosis [ 34 , 43 ]. Previous studies have reported increased autophagic activity in tubular cells in human biopsy samples from transplanted kidneys [ 44 ] and patients with renal disease [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, another study found that autophagy induced by the transcription factor EB can mediate the apoptosis of TECs, thereby aggravating the progression of renal fibrosis [ 10 ]. In a rat model of renal fibrosis following unilateral ureteral ligation (UUO), downregulation of autophagy alleviates disease progression [ 11 ]. The mechanisms of autophagy involved in renal fibrosis are complex, but it is certainly an attractive target in the search for therapeutic approaches to CKD.…”
Section: Introductionmentioning
confidence: 99%